2013
DOI: 10.1123/ijsnem.23.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Ad Libitum Fluid Intake Does Not Prevent Dehydration in Suboptimally Hydrated Young Soccer Players During a Training Session of a Summer Camp

Abstract: Approximately 90% of the young soccer players who began exercising under warm weather conditions were hypohydrated, while drinking ad libitum during practice did not prevent further dehydration in already dehydrated players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 43 publications
6
30
1
12
Order By: Relevance
“…The body weight and USG data indicate the sailors were becoming hypohydrated with concomitant increases in thirst sensation. These findings are in agreement with Arnaoutis et al, which found that ad libitum fluid intake did not prevent dehydration in 54 of 66 (82%) young soccer players that started their practice with USG greater than 1.020 during a summer camp (Arnaoutis et al, 2013). Two studies have examined change in performance and physiological markers in young athletes with similar values of dehydration exhibited in the current study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The body weight and USG data indicate the sailors were becoming hypohydrated with concomitant increases in thirst sensation. These findings are in agreement with Arnaoutis et al, which found that ad libitum fluid intake did not prevent dehydration in 54 of 66 (82%) young soccer players that started their practice with USG greater than 1.020 during a summer camp (Arnaoutis et al, 2013). Two studies have examined change in performance and physiological markers in young athletes with similar values of dehydration exhibited in the current study.…”
Section: Discussionsupporting
confidence: 81%
“…The data collected in the current study align with previous studies suggesting young athletes arrive to competition underhydrated (Arnaoutis et al, 2015;Arnaoutis et al, 2013;Da Silva et al, 2012;Yeargin et al, 2010). On day 3 and day 4 of the competition sailors arrived with USG greater than 1.020, a value indicative of suboptimal hydration (Sawka et al, 2007 (McDermott et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…En varios estudios [6][7][8]10,17,18 se muestra que los jugadores no fueron capaces de reemplazar las pérdidas de agua por sudoración mediante la ingesta de agua ad libitum, como en el presente ensayo, mientras que otro estudio 24 obtuvo que una ingesta de líquido previamente prescrita se tradujo en una mayor ingesta por parte de los jugadores. Por lo que la prescripción de una ingesta determinada podría llegar a conseguir una mayor ingestión de agua y así disminuir la tasa de deshidratación durante la práctica deportiva.…”
Section: Discussionunclassified
“…Se determinó que los jugadores únicamente reemplazaron el 50% de la pérdida de agua corporal por sudoración por lo que sería necesario estrategias para mejorar la reposición de agua corporal para los jugadores que compiten en ambientes calurosos 7 . En otra investigación se evaluó el estado previo de hidratación y el balance hí-drico en 107 jugadores con unas condiciones ambientales de 27,2±2°C y 57±9% de humedad relativa donde se analizó el estado de hidratación a través del color y de la gravedad específica de la orina y a partir de cambios en el peso 8 . En dicha investigación se observó que el 90% de los jugadores comenzaron el entrenamiento en un estado de hipohidratación así como que el consumo ad libitum de agua no evitó una mayor deshidratación en la muestra analizada.…”
unclassified
“…Preliminary evidence demonstrates a link between hydration and physical performance in children: improving hydration by providing education regarding the importance of hydration, a urine color scale [41] to assess the hydration before and after exercise, and by improving water access resulted in increased performance during an endurance run by athletic children [42]. This is relevant since some studies suggest that a majority of child athletes may be insufficiently hydrated before they start exercising [43,44]. While there are limited data concerning preexercise hydration status of children from the general population, research suggests that many of them have elevated urine concentration on a given "normal" day across various countries [45][46][47][48][49].…”
Section: Hydration Assessment Of Childrenmentioning
confidence: 99%